Elevated troponin in hematopoietic stem cell transplantation-associated thrombotic microangiopathy: A case report - Lili Zhou; Ying Wang; Fei Zhou; Xiao Ma; Xuefeng He, MD, PhD (Thrombosis Update, 2020)
Elevated troponin was associated with poor prognosis during thrombotic microangiopathy (TMA) in several reports, but elevated troponin in haploidentical hematopoietic stem cell transplantation-associated thrombotic microangiopathy (TATMA) has not yet been reported. Here, we report the first case of elevated troponin, which was inferred to be related to TA-TMA in our center. This finding demonstrates that we should focus on the elevated troponin in TA-TMA.